Peatland-based innovation can potentially support and enable the sustainable development goals of the United Nations: Case study from the Republic of Ireland. (December 2022) - O'Neill, Emer A.; McKeon Bennett, Michelle; Rowan, Neil J.
Abstract: The aim of this case study is to develop a novel freshwater aquaculture organic-process in the Irish peatlands along with adjacent eco-innovation that will support food production and security regionally with a global orientation. This specifically addresses the problem of traditional workforce reliance on burning peat as a fossil fuel by providing alternative green-friendly eco-innovative activities for new employment and social enterprise. Findings show that this system relies upon a naturally-occurring ecosystem of algae, bacteria and duckweed species to achieve effective waste remediation and for water quality. There is no use of artificial compounds including antibiotics, and no discharge of effluent to receiving waters. Peatlands are a unique ecosystem that constitute an important carbon sink, but also represents a novel environment for climate solutions. This novel peatland-site holds the potential to support the sustainable development goals of the United Nations as described herein. Graphical abstract: Image 1